The Beneficial Effects of Moxibustion on Overweight Adolescent Girls. (11th May 2021) - Yeh, Yuan-Chieh; Chen, Chin-Chang; Cheng, Ching-Yi; Chang, Hsin-Ning; Huang, Tse-Hung
Abstract : Among adolescent girls, overweight or obesity has both physical and psychological involvement. We conducted a randomized controlled trial of moxibustion using a moxa burner. Fifty-four eligible girls aged 15–18 years with a body mass index (BMI) greater than 25.3 were enrolled in the study. The girls were randomly allocated to the treatment ( n  = 27) and control ( n  = 27) groups. The girls underwent treatment three times per week for 8 weeks (24 treatments). Moxibustion was applied to the RN12, RN6, ST25, ST36, and SP6 acupoints. Physical assessments were BMI, waist-to-hip ratio (WHR), and body fat ratio (BFR). Psychological outcomes were measured using the Rosenberg Self-Esteem Scale (RSE). Data were collected at the beginning of the study (baseline), week 4, and week 8. Of the 54 participants, 46 completed the trial. The difference in mean BMI from baseline between the two groups was 0.097 (p = 0.655 ) at week 4 and −0.794 (p = 0.001 ) at week 8. The mean WHR of the treatment group was significantly reduced compared with baseline, with a −0.011 (p = 0.017 ) and −0.035 (p < 0.001 ) mean change at weeks 4 and 8, respectively. The mean BFR was slightly reduced (−0.253;p = 0.474 ) at week 4 compared with baseline in the treatment group. At week 8, it was significantly reduced (−2.068; p < 0.001 ) from baseline in the treatment group. The mean RSE in the treatment group showed no significant increase from baseline at week 4 (0.155 points, p = 0.803 ), but it improved significantly from baseline at week 8 (1.606 points, p = 0.021 ) compared to that in the control group. No obvious adverse effect was reported during this study. Moxibustion using a moxa burner may be an effective and safe intervention for overweight adolescent girls, having both physical and psychological benefits.